2011
DOI: 10.1590/s0034-89102011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Percepção do ambiente e prática de atividade física em adultos residentes em região de baixo nível socioeconômico

Abstract: OBJECTIVE:To analyze the association between practice of physical activity and the perception of the community environment among adults. METHODS:A cross-sectional study of 890 adults carried out in Ermelino Matarazzo district in São Paulo, Southeastern Brazil, 2007. The dependent variables were the practice of at least 150 minutes per week in leisure time physical activity and walking for commuting. Independent variables concerned the environment, and adjustment variables were sex, age, education and length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
39

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 22 publications
4
34
1
39
Order By: Relevance
“…Los resultados del presente estudio confirman la influencia del ambiente físico y social del barrio en la percepción de los sujetos para caminar y andar en bicicleta, aspecto reportado por investigadores de diferentes regiones del mundo (26)(27)(28) . La evidencia sugiere que residir en barrios de escasos recursos económicos confiere un mayor riesgo para inactividad física, independiente de las circunstancias socioeconómicas individuales (18) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados del presente estudio confirman la influencia del ambiente físico y social del barrio en la percepción de los sujetos para caminar y andar en bicicleta, aspecto reportado por investigadores de diferentes regiones del mundo (26)(27)(28) . La evidencia sugiere que residir en barrios de escasos recursos económicos confiere un mayor riesgo para inactividad física, independiente de las circunstancias socioeconómicas individuales (18) .…”
Section: Discussionunclassified
“…Se halló en este estudio que la percepción de inseguridad para caminar y montar bicicleta durante el día está determinado por el barrio donde habitan los sujetos, lo cual ha sido documentado en varios estudios (26) , cuando las personas perciben que la seguridad de su barrio es positiva son más activos físicamente. Al respecto Parra 34 , comenta que la percepción personal de seguridad está positivamente asociada con caminar como transporte.…”
Section: Discussionunclassified
“…Some of our results are consistent with this pattern. On the other hand, in Brazil, open public settings for group sports are usually found in low socioeconomic areas and are sometimes the only sites available for LTPA 23 . Other researchers have observed that group sports settings are associated with more LTPA in adults with low educational levels 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The scale assesses different aspects of the physical environment that can favor walking and the practice of physical activity in leisure and movement. (14) The first part contains 18 questions about availability and proximity of leisure structures, services and conveniences in the neighborhood, which are less than a ten-minute walk from home. The second part contains 20 questions related to the availability and quality of environmental structures (green areas, sidewalks, garbage accumulation) close to the patient's home, perceived safety in traffic and environment, social support, climate, and the presence of pets at home.…”
Section: Methodsmentioning
confidence: 99%